Pengembangan Media Pembelajaran AKFI (Akidah Akhlak Fun Learning) berbasis PowerPoint Interaktif pada Mata Pelajaran Akidah Akhlak di MA Al-Bairuny Sambongdukuh Jombang - Marensa, Grishelda Augusta; Nisa’, Khoirun; Wahyudi, Wahyudi (YASIN, 2025)
The teaching of Akidah Akhlak in schools often faces challenges in creating an engaging and interactive learning environment, necessitating innovative learning media that can enhance student involvement while strengthening content comprehension. This study aims to develop an interactive PowerPoint-based learning medium, AKFI (Akidah Akhlak Fun Learning), focused on the topic of zulm (wrongdoing), and to assess its feasibility and effectiveness. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The study involved 22 students from class X IPS 1 at MA Al-Bairuny Sambongdukuh, Jombang. Validation results indicated a very high level of feasibility, with scores of 92% from the subject matter expert and 97.34% from the media expert. Field testing yielded a score of 89.32%, falling within the "highly appropriate" category. These findings demonstrate that the AKFI media is both feasible and effective in enhancing the quality of Akidah Akhlak learning, and is well aligned with student needs and characteristics.